African-American Males in Prison: Are they Doing Time or is the Time Doing Them? - King, Anthony E. O. (1993)
African-American males comprise a disproportionate percentage of the individuals imprisoned in State correctional institutions across the United States. The purpose of this paper is to describe how incarceration affects African-American males. The author recommends more rigorous and systematic analysis of the prison experience, and how it affects the mental, physical, and social well-being of African-American males. Given this nation's commitment to using imprisonment as the principal means for punishing convicted felons, it is imperative that society ascertain the social, psychological, and economic effects of such confinement on millions of African-American males